HBA1C SEBAGAI KANDIDAT BIOMARKER UNTUK PREDIKSI PROGESIVITAS GANGGUAN KOGNITIF TERKAIT DIABETES MELITUS TIPE 2 - Putri Nurhayati; Achmad Mujahidin Irham; I Dewa Bagus Ketut Widya Pramana; Herpan Syafii Harahap (Faculty of Medicine Universitas Mataram, 2022)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by insulin resistance and hyperglycemia which underlie its complications, including cognitive impairment. T2dm-associated cognitive impairment is generally characterized by the decrease in at least one cognitive domain. However, its progression can be slowed by appropriate blood glucose control. Hb1Ac is a candidate of appropriate biomarker in predicting the progression of T2DM-associated cognitive impairment. This is based on several important characteristics it has, including a good blood glucose index, low daily biological variability, relatively unaffected by stress conditions, and unaffected by variations due to loading the amount of glucose.